Association between triglycerides and lumbar bone mineral density in Chinese patients with osteoporotic fractures: a retrospective cross-sectional study - Peng Zhou; Lei Liu; Ke Lu; Min-zhe Xu; Yao-wei Ye; Chong Li; Yi Yin (Scientific Reports)
Abstract The association between lumbar bone mineral density (BMD) and triglyceride (TG) levels has been extensively studied; however, the results remain controversial. Therefore, this research aimed to elucidate the association of TG levels with lumbar BMD in patients with osteoporotic fractures (OPFs) who have undergone surgery. This cross-sectional study analyzed 3,558 OPF patients (aged 50 years and above) who were admitted to the First People’s Hospital of Kunshan and assessed their TG levels, lumbar BMD, and other variables. The outcome variable of this research was bone density, whereas the baseline glycerol trihydrate levels were considered as the exposure variable. An analysis adjustment was conducted for various covariates, including age, gender, body mass index (BMI), and other baseline laboratory and clinical results. Furthermore, the potential non-linear relationships were assessed via the smooth curve fitting, and threshold effect analyses. The mean age of 3,558 included OPF patients was 68.87 ± 10.55 years. In the fully adjusted multivariate regression analysis, a positive correlation was found between TG levels and lumbar BMD (β = 0.015, 95% CI: 0.001–0.028, p = 0.033). Furthermore, the threshold effect analysis revealed a curvilinear relationship between TG levels and lumbar BMD, with a turning point at 1.26 mmol/L. Moreover, on both sides of the turning point, different patterns were observed. On the left side, TG levels were positively correlated with lumbar BMD. However, despite higher TG levels, the differences in lumbar BMD on the right side of the turning point, were not statistically significant, indicating a lack of significant association (p = 0.712). In summary, this research indicated that in OPF patients, higher TG levels were significantly positively associated with lumbar BMD. Furthermore, there was a threshold value of 1.26 mmol/L, indicating that TG levels in OPF patients with concomitant hypertriglyceridemia should be maintained within the normal range, and reducing TG levels below 1.26 mmol/L requires continuous monitoring. This approach effectively controls TG levels without adversely impacting lumbar BMD.